Dehumanization of Women by Da'iyah (Media Contest in Religious Lectures) - Nurun Najwah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The dehumanization of women in the religious framework in the media is in the form of defining women as